If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + 6 = 1c Reorder the terms: 6 + 2y = 1c Solving 6 + 2y = 1c Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 2y = -6 + 1c Combine like terms: 6 + -6 = 0 0 + 2y = -6 + 1c 2y = -6 + 1c Divide each side by '2'. y = -3 + 0.5c Simplifying y = -3 + 0.5c
| 8m-14=6m+8 | | 1.14=x-10/3 | | B+3=9+b | | 8(q+4)=-4q | | 18x+20+x=5+10x-3 | | 8/7=x/3-10/3 | | 8x+20+x=5+10x-3 | | 5x+24=2+7(-8-3x) | | 3x+10+5x-5+15=180 | | 14.2/0.8 | | (x+6)(x-1)=78 | | 3x+10+5x-5=120 | | 10+2a-2+3a= | | 0=40+a(5) | | 660/100 | | 7s/2+7=9 | | 3x+10=120 | | 25x^3+20x^2+4x=0 | | 25/0=100/X | | 85=15x | | y=-8x^2+12x+14 | | 15(11-6x)-10(9+12x)=285 | | (x+12)(x-15)=0 | | (5x+3)/4=-12 | | 7-9(5t-4)=47 | | 7/4x+4/3=-8 | | x=0.1666666667 | | 15c+12=2 | | 110-x=11 | | 2(1+3x)=26 | | 3t-(t+5)=6+(t+1) | | 3(4p+5)-11p= |